1994
DOI: 10.1159/000119069
|View full text |Cite
|
Sign up to set email alerts
|

Antihistamine Effects on the Central Nervous System, Cognitive Performance and Subjective States

Abstract: Diphenhydramine causes drowsiness and performance decrements in some tasks whereas terfenadine generally does not. This study examined central nervous system (CNS) differences in response to the administration of diphenhydramine (50 mg) and terfenadine (60 mg) up to 3 h after drug administration. Two evoked potential measures, the Brainstem Auditory Evoked Potential and the Pattern Reversal Evoked Potential (PREP), assessed CNS function. Other measures of CNS function, cognitive performance and subjective stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…In the current study we found that responses were significantly slower and less accurate following ingestion of diphenhydramine relative to the other test conditions. Similar effects have been observed in prior studies that have examined performance following diphenhydramine administration in subject populations and under dosing ranges and procedural conditions approximating those in the current study (Fine et al 1994b;Oken et al 1995;Rice and Snyder 1993;Tharion et al 1994). Of particular interest is the observation that the behavioral impairment produced by 50 mg of diphenhydramine was substantially greater than the behavioral change observed following a dose of alcohol adequate to raise blood alcohol to the Figure 7.…”
Section: Changes In Task Performance Following Treatment With Caffeinsupporting
confidence: 81%
“…In the current study we found that responses were significantly slower and less accurate following ingestion of diphenhydramine relative to the other test conditions. Similar effects have been observed in prior studies that have examined performance following diphenhydramine administration in subject populations and under dosing ranges and procedural conditions approximating those in the current study (Fine et al 1994b;Oken et al 1995;Rice and Snyder 1993;Tharion et al 1994). Of particular interest is the observation that the behavioral impairment produced by 50 mg of diphenhydramine was substantially greater than the behavioral change observed following a dose of alcohol adequate to raise blood alcohol to the Figure 7.…”
Section: Changes In Task Performance Following Treatment With Caffeinsupporting
confidence: 81%
“…Tests of car driving feature in 15 studies and appear to be sensitive to the sedative effects of antihistamines. It has been suggested that the ability of the driver to control weaving of the car, measured as the standard deviation of the lateral position, is an indicator of drug‐induced sedation [7]. Such tests represent low level global motor performance and do not assess more important functions, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that these newer, non-sedating antihistamines have few, if any, negative effects in comparison to the earlier H 1 -blocker antihistamines. For example, it has been shown that newer, non-sedating antihistamines have no apparent negative effects on various cognitive and psychomotor abilities (Cingi, Cingi, & Cingi, 1990;Clarke & Nicholson, 1978;Fink & Irwin, 1979;Kulshrestha, Gupta, Turner, & Wadsworth, 1978;Nesthus, Schiflett, Eddy, & Whitmore, 1991;Nicholson & Stone, 1982;Nicholson & Stone, 1986;Philpot, Biegalski, & Brooker, 1993;Reeves, Blackwell, Molina, & Hixson, 1989;Rice & Snyder, 1993;Snyder & Berg, 1990;Tharion, McMenemy, & Rauch, 1994;Witek, Canestrari, Miller, Yang, & Riker, 1995). They also do not appear to disrupt EEG activity (Loring & Meador, 1989;Stephens, Caldwell, Comperatore, Pearson, & Delrie, 1992;Tharion et al, 1994) or more basic sensory-psychophysical functions (Fink & Irwin, 1979;Kulshrestha et al, 1978;Nicholson, Smith, & Spencer, 1982;Nicholson & Stone, 1982;Nicholson & Stone, 1986), and they do not typically influence self-reported levels of subjec-• tive state (Philpot et al, 1993;Reeves et al, 1989;Tharion et al, 1994).…”
Section: Antihistaminesmentioning
confidence: 99%